ETIKA BISNIS ISLAM DAN DAMPAKNYA TERHADAP KESEJAHTERAAN PEDAGANG SAPI - AHMAD HULAIMI; SAHRI SAHRI; MOH. HUZAINI (JEBI (Jurnal Ekonomi dan Bisnis Islam), 2017)
The theme of the article is "economy based on the principles of Islam". This study aims to determine the business ethics of Islam being implemented, and its impact on the welfare of cattle traders. The method used is qualitative descriptive. This type of research is a field research. The results of this study found that Islamic business ethics applied by cattle traders in the Masbagik not yet fully apply the principles of Islamic ethics. Not all cattle traders get welfare because of not fulfilling the needs dharuriyat.